2014
DOI: 10.1038/gim.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioral research in genomic sequencing: approaches from the Clinical Sequencing Exploratory Research Consortium Outcomes and Measures Working Group

Abstract: The routine use of genomic sequencing in clinical medicine has the potential to dramatically alter patient care and medical outcomes. To fully understand the psychosocial and behavioral impact of sequencing integration into clinical practice, it is imperative that we identify the factors that influence sequencing-related decision making and patient outcomes. In an effort to develop a collaborative and conceptually grounded approach to studying sequencing adoption, members of the National Human Genome Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 71 publications
1
69
1
Order By: Relevance
“…A study by Sanderson et al [22] found that hypothetical interest in genetic testing only modestly reflects future testing behaviour. Other studies have shown that expressed preferences for receiving genetic risk information and intentions to modify behaviour are not necessarily predictive of future preferences and behaviour change [4,6]. Therefore, participants' views in our study may differ to the actual implementation of the proposed intervention.…”
Section: Discussioncontrasting
confidence: 39%
See 4 more Smart Citations
“…A study by Sanderson et al [22] found that hypothetical interest in genetic testing only modestly reflects future testing behaviour. Other studies have shown that expressed preferences for receiving genetic risk information and intentions to modify behaviour are not necessarily predictive of future preferences and behaviour change [4,6]. Therefore, participants' views in our study may differ to the actual implementation of the proposed intervention.…”
Section: Discussioncontrasting
confidence: 39%
“…Our focus group participants believed that a negative emotional or psychological response would be more likely if the recipient misunderstood the personalised genomic risk information. An analysis of social and behavioural research related to delivery of genomic sequencing results in clinical practice found that most studies demonstrated either no change or a decrease in negative emotions such as anxiety or depression compared to prior levels after receipt of genetic risk information, even when individuals receive results reporting increased disease susceptibility [6]. A Cochrane systematic review [4] also found no evidence that communicating DNA-based disease risk had detrimental psychological effects, however the quality of included studies was generally poor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations